A case report of eosinophilic enterocolitis - Chundempetta, Daniyah C. H.; Legha, R. (International Journal of Research in Medical Sciences, 2023)
A 13-year-old boy was admitted with complaints of abdominal pain and loose stools. Abdomen was distended. Laboratory tests on admission revealed neutrophilic leukocytosis and a peripheral smear done showed severe eosinophilia (33%) and leukocytosis. CT abdomen revealed ascites. Ascitic fluid tapping was done and 1.5 L of straw colored ascitic fluid drained. Ascitic fluid study was suggestive of high protein low SAAG ascites. The possibility of eosinophilic enterocolitis was considered. For confirmation endoscopy and sigmoidoscopy were done and a segmental biopsy was taken. Biopsy was suggestive of significant mucosal eosinophilia of duodenum, stomach, rectum, and eosinophilic abscess in the muscularis layer in the duodenum, stomach, and descending colon.